2019
DOI: 10.1186/s12961-019-0477-3
|View full text |Cite
|
Sign up to set email alerts
|

A framework for value-creating learning health systems

Abstract: Background Interest in value-based healthcare, generally defined as providing better care at lower cost, has grown worldwide, and learning health systems (LHSs) have been proposed as a key strategy for improving value in healthcare. LHSs are emerging around the world and aim to leverage advancements in science, technology and practice to improve health system performance at lower cost. However, there remains much uncertainty around the implementation of LHSs and the distinctive features of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
311
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(318 citation statements)
references
References 74 publications
7
311
0
Order By: Relevance
“…Transparent and iterative, cyclical improvement processes in the LHS to enable timely access, sharing and streamlined linkage of data, with mechanisms to feedback into frontline care, were recognised as important in ensuring the LHS approach was impactful and sustainable. These ndings are commensurate with the emerging literature that describes systematic approaches and processes that are common in all LHS environments [2,9,11,[24][25][26].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Transparent and iterative, cyclical improvement processes in the LHS to enable timely access, sharing and streamlined linkage of data, with mechanisms to feedback into frontline care, were recognised as important in ensuring the LHS approach was impactful and sustainable. These ndings are commensurate with the emerging literature that describes systematic approaches and processes that are common in all LHS environments [2,9,11,[24][25][26].…”
Section: Discussionsupporting
confidence: 80%
“…Data access, systems and processes to producing useable, useful and quality data was identi ed as a theme and is generally reported in literature on the impact of LHS models [3,[8][9][10][11]. We found that appropriate infrastructure and transparent processes are reportedly needed to operationalise data access, linkage, analysis and applications.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Data access, systems and processes to producing useable, useful and quality data was identi ed as a theme and is generally reported in literature on the impact of LHS models [3,[8][9][10][11]. We found that appropriate infrastructure and transparent processes are required to operationalise data access, linkage, analysis and applications.…”
Section: Discussionmentioning
confidence: 88%
“…The elements of the programme theory are presented in a conceptual framework that identifies seven contextual factors acting as enablers or barriers to the functioning of the intended theory, some of which appeared to have the potential to hinder or even derail the health service's research impact expectations and ambitions. By identifying both impact types and contextual factors, this study and the planned research impact evaluation contribute to an identified need for empirical examination of how "learning healthcare systems", that is health systems that intertwine production and implementation of evidence with routine healthcare, are enacted in practice [24], including how they deliver "value" in clinical settings [25].…”
Section: Discussionmentioning
confidence: 99%